The Impact of Educational Videos as a Tool to Enhance Information Shared With Students Regarding Recent Trends in Fashion Advertising - Al-Dabbagh et al., Maha Abdullah (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to propose a teaching method for the curriculum of Fashion advertising within Art inspiration (Doctoral Program). king Abdelaziz university. This made researchers to design an educational video to assess the effects of modern art trends on fashion advertising as well as enabling students to comprehend the information in few minutes. The research has followed the semi-experimental approach through an e-questionnaire to measure the effectiveness of this developed approach. The search sample was formed from. Doctoral program students in the Department of Clothing and Textile. The results showed that there are statistically significant differences in favor of the after test. The researchers recommended applying this proposed method to doctoral students and motivate them for self-learning by using different educational aids (SCL).